Understanding Local Spatial Variation Along the Care Continuum: The Potential Impact of Transportation Vulnerability on HIV Linkage to Care and Viral Suppression in High-Poverty Areas, Atlanta, Georgia. (1st May 2016) - Goswami, Neela D.; Schmitz, Michelle M.; Sanchez, Travis; Dasgupta, Sharoda; Sullivan, Patrick; Cooper, Hannah; Rane, Deepali; Kelly, Jane; del Rio, Carlos; Waller, Lance A.
Abstract : Background: Engagement in care is central to reducing mortality for HIV-infected persons and achieving the White House National AIDS Strategy of 80% viral suppression in the US by 2020. Where an HIV-infected person lives impacts his or her ability to achieve viral suppression. Reliable transportation access for healthcare may be a key determinant of this place-suppression relationship. Methods: ZIP code tabulation areas (ZCTAs) were the units of analysis. We used geospatial and ecologic analyses to examine spatial distributions of neighborhood-level variables (eg, transportation accessibility) and associations with: (1) community linkage to care, and (2) community viral suppression. Among Atlanta ZCTAs with data for newly diagnosed HIV cases (2006–2010), we used Moran I to evaluate spatial clustering and linear regression models to evaluate associations between neighborhood variables and outcomes. Results: In 100 ZCTAs with 8413 newly diagnosed HIV-positive residents, a median of 60 HIV cases were diagnosed per ZCTA during the 5-year period. We found significant clustering of ZCTAs with low linkage to care and viral suppression (Moran I = 0.218, P < 0.05). In high-poverty ZCTAs, a 10% point increase in ZCTA-level household vehicle ownership was associated with a 4% point increase in linkage to care ( P = 0.02, R 2 = 0.16). In low-poverty ZCTAs, a 10% point increase in ZCTA-level household vehicle ownership was associated with a 30% point increase in ZCTA-level viral suppression ( P = 0.01, R 2 = 0.08). Conclusions: Correlations between transportation variables and community-level care linkage and viral suppression vary by area poverty level and provide opportunities for interventions beyond individual-level factors.